Nematode infection patterns in a Neotropical lizard species from an insular mountain habitat in Brazil - Václav, A. B.H.P.; Anjos, L. A. [UNESP]; Queiróz, M. S. [UNESP]; Nascimento, L. B.; Galdino, C. A.B. (Cambridge University Press (CUP), 2017)
Neotropical lizards are known to harbour rich nematode parasite faunas; however, knowledge of the diversity and patterns of infection are still lacking for many species. This is true for the genus Tropidurus, in which data on patterns of parasitism are known for only approximately 11 of its 30 species. We show that the nematode fauna associated with a population of Tropidurus montanus is composed of three species of host-generalist parasites with high overall prevalence. Male and female lizards did not differ in infection pattern and there was no relationship between host body size and intensity of infection for the most prevalent parasite species. Nevertheless, overall prevalence changed seasonally, with a higher proportion of parasitized individuals being found in the dry period than in the rainy period. We discuss our findings in the context of diet patterns of T. montanus, which we suggest may explain the similarities in prevalence and intensity of infection between the sexes. In addition, seasonal changes in diet are considered to be related to the observed differences in prevalence between dry and rainy periods.